A novel halophilic Exiguobacterium mexicanum strain removes nitrogen from saline wastewater via heterotrophic nitrification and aerobic denitrification. (August 2021) - Cui, Yuan; Cui, You-Wei; Huang, Ji-Lin
Graphical abstract: Highlights: A slightly halophilic strain with HN-AD function was isolated. The HN-AD pathway follows NH4 +  → NO2 −  → N2 . 83.2% of ammonium was converted into nitrogen gas. High NH4 + -N removal can be achieved in saline (3–5% w/v) wastewater. Abstract: The utilization of halophilic bioresources is limited due to a lack of isolation and characterization work. A halophilic bacterium strain SND-01 of Exiguobacterium mexicanum was isolated in this study, which is the first report on its novel function in heterotrophic nitrification-aerobic denitrification (HN-AD). The strain SND-01 is slightly halophilic, surviving at 0 up to 9% (w/v) salinity. When utilizing ammonium, nitrate or nitrite as the sole nitrogen source in aerobic conditions, the isolated strain showed the maximum nitrogen removal rate of 2.24 ± 0.14 mg/(L·h), 3.63 ± 0.21 mg/(L·h) and 2.30 ± 0.23 mg/(L·h), respectively. Functional genes and key enzymes involved in heterotrophic-aerobic nitrogen transformations were characterized, establishing the pathway of HN-AD. The nitrogen removal via HN-AD is dependent on the C/N ratio, salinity and temperature. The halophilic Exiguobacterium mexicanum strain SND-01 shows a significant potential in biotreatment of saline wastewater in an easy and cost-effective way.